EFEKTIVITAS PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) BPJS KESEHATAN DALAM MENINGKATKAN KUNJUNGAN PASIEN DAN PELAYANAN KESEHATAN DI KLINIK MATA PANDAAN - Zainita, Ratri (Prodi Magister Manajemen Universitas Wijaya Putra, 2024)
This study aims to analyze the effectiveness of the National Health Insurance (JKN) BPJS Kesehatan program in increasing patient visits and health services at Pandan Eye Clinic. The research method used is quantitative with a descriptive and analytical approach. Data was collected through documentation studies, interviews, and observations. The results of the study show that the JKN BPJS Kesehatan program has increased patient visits and the types of health services at Pandaan Eye Clinic. JKN BPJS Kesehatan patients are also satisfied with the health services they receive. In conclusion, the JKN BPJS Kesehatan program has been proven effective in increasing access to and quality of health services at Pandan Eye Clinic.